Analysis Of Student's Learning Activity And Creative Thinking In Face-To-Face Learning Limited In The Transition Period: ANALISIS KEAKTIFAN BELAJAR DAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN TATAP MUKA TERBATAS PADA MASA TRANSISI - Mahmudah; Ghina Amaliatul Khasanah; Makherus Sholeh (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2022)
The purpose of this research is to determine the activeness of students' learning and creative thinking of students while face-to-face learning is limited to the transition period in thematic subjects of grade VI elementary school. The form of research used is qualitative. The subjects in this study were homeroom teachers and students of class VI Darul Hijrah, Kelumpang Hilir District, Kotabaru Regency, totaling 20 students, for the 2021/2022 school year. The respondents that the researchers succeeded in getting were as many as 20 populations. Data collection techniques used are question and answer and direct observation. The results of the study stated that 75% of student learning activities were in the good category, namely students were able to achieve the parameters of student learning activity. Meanwhile, students' creative thinking skills at the time of face-to-face learning were limited to 68% in the good category, and were able to achieve the parameters of creative thinking abilities ABSTRAK: